2009
DOI: 10.1021/nl803279t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-Doped Graphene by Chemical Vapor Deposition and Its Electrical Properties

Abstract: To realize graphene-based electronics, various types of graphene are required; thus, modulation of its electrical properties is of great importance. Theoretic studies show that intentional doping is a promising route for this goal, and the doped graphene might promise fascinating properties and widespread applications. However, there is no experimental example and electrical testing of the substitutionally doped graphene up to date. Here, we synthesize the N-doped graphene by a chemical vapor deposition (CVD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

80
1,979
3
15

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,903 publications
(2,077 citation statements)
references
References 71 publications
80
1,979
3
15
Order By: Relevance
“…All our samples exhibit a prominent D band ( Figure 1c and Figure S1b), whose intensity is reported to reflect the level of N-dopant concentration in the graphene sheets. 17,34,35 The intensities of the D band exhibit a clear reduction in the films grown at higher temperatures ( Figure S1b). In addition, all the Ndoped graphene films display a strong 2D band, indicating that the as-grown films are of high crystal quality ( Figure 1c and Figure S1b).…”
Section: Scanning Tunneling Microscope (Stm) Measurements Were Performentioning
confidence: 99%
See 1 more Smart Citation
“…All our samples exhibit a prominent D band ( Figure 1c and Figure S1b), whose intensity is reported to reflect the level of N-dopant concentration in the graphene sheets. 17,34,35 The intensities of the D band exhibit a clear reduction in the films grown at higher temperatures ( Figure S1b). In addition, all the Ndoped graphene films display a strong 2D band, indicating that the as-grown films are of high crystal quality ( Figure 1c and Figure S1b).…”
Section: Scanning Tunneling Microscope (Stm) Measurements Were Performentioning
confidence: 99%
“…Ndoped graphene has been employed for various applications including, e.g., realizations of ultracapacitors, 15 lithium batteries, 16 and field-effect transistors. 17 Theoretical calculations and recent experiments have revealed that among the three predominant types of C-N bonding configurations (i.e., graphitic N, pyridinic N, and pyrrolic N configurations) in graphene, [18][19][20][21] only graphitic N-doping (i.e., substitutional N doping) could both bring ntype doping to graphene and preserve high mobility. (Here, it should be noted that other methods, such as atomic hydrogen adsorption, could also induce n-type doping in graphene.…”
mentioning
confidence: 99%
“…The sheet resistance of N-doped graphene is reported to be higher compared to graphene, which is explained by a n-type semiconductor behavior leading to a decrease in conductivity. 25 The values listed in Table 3 Table 3 Peak positions and linewidths (in cm −1 ) of D, G and D' bands and intensity ratios of D, G, D' and 2D peaks in the Raman spectra (488 nm excitation with 2 mW power) of transferred graphene sheets on glass.…”
Section: Optical and Electronic Characterizationmentioning
confidence: 99%
“…24 So far, few methods for generating N-doped graphene are described. Among these are thermal CVD of methane and ammonia gas, 25 CVD of molecular precursors like pyridine 26 or acetonitrile 27 on a Cu substrate or exposure of graphene to a nitrogen 28 or ammonia 29 containing plasma discharge.…”
mentioning
confidence: 99%
“…Compared to traditional doping processes (e.g., chemical vapor deposition; segregation growth and post treatment, etc. ), the conditions employed for this thermal process were relatively mild 10. In this study, the sodium storage properties of S‐SG and pristine SG have been investigated.…”
mentioning
confidence: 99%